2017
DOI: 10.14310/horm.2002.1730
|View full text |Cite
|
Sign up to set email alerts
|

PTH and PTHR1 in osteocytes. New insights into old partners

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 79 publications
0
7
0
Order By: Relevance
“…Nevertheless, the mechanism whereby PTH prevents osteocyte apoptosis remains ill-defined. As noted, it was reported that activation of PTH1R in osteocytes could promote gap junction-mediated intercellular coupling, increase expression of MMP-9, and potentiate calcium influx via stretch-activated Ca i 2+ channels, as well as amply the osteogenic response to mechanical loading in vivo, therefore leading to protect osteocytes from apoptosis 135 . Consistent with this notion, it is suggested that G-protein coupled receptors (GPCR) may participate in the cell transduction of mechanical signals, PTH1R and stretch-activated Ca i 2+ channels might both be part of the same mechanosensor system 136 .…”
Section: The Key Molecular Mechanisms In Preserving the Osteocytic VImentioning
confidence: 96%
“…Nevertheless, the mechanism whereby PTH prevents osteocyte apoptosis remains ill-defined. As noted, it was reported that activation of PTH1R in osteocytes could promote gap junction-mediated intercellular coupling, increase expression of MMP-9, and potentiate calcium influx via stretch-activated Ca i 2+ channels, as well as amply the osteogenic response to mechanical loading in vivo, therefore leading to protect osteocytes from apoptosis 135 . Consistent with this notion, it is suggested that G-protein coupled receptors (GPCR) may participate in the cell transduction of mechanical signals, PTH1R and stretch-activated Ca i 2+ channels might both be part of the same mechanosensor system 136 .…”
Section: The Key Molecular Mechanisms In Preserving the Osteocytic VImentioning
confidence: 96%
“…However, when PTH-mediated signaling leads to the phosphorylation and inactivation of SIK2, this allows HDAC4 and HDAC5 to translocate into the nucleus. Within the nucleus, HDAC4 and HDAC5 act to inhibit the function of MEF2C [ 191 ], a transcription factor that normally drives the expression of the Sost gene, which is known to encode a protein that inhibits bone formation. Simultaneously, the inactivated SIK2 reduces the phosphorylation of CREB-regulated transcription coactivator 2 (CRTC2) and leads to its dephosphorylation by an unknown phosphatase, therefore promoting its nuclear translocation.…”
Section: The Direct Interactions Of Pth With Bm Cellsmentioning
confidence: 99%
“…Since SIK2 suppression leads to the regulation of key PTH target genes in osteocytes, not surprisingly, small molecular SIK2 inhibitors such as YKL05099 mimic many of the effects of PTH in osteocytes and following in vivo administration [ 191 ]. Overall, these observations indicate that SIK inhibition is a key signaling mechanism used by PTH to accomplish its physiologic effects in osteocytes.…”
Section: The Direct Interactions Of Pth With Bm Cellsmentioning
confidence: 99%
“…PTH subsequently stimulates calcium resorption from bone and bone formation. PTH receptors (PTH1 receptor) are most highly expressed in osteocytes, which are also the most abundant cell type in the bone ( 251 ). Activation of these receptors, which are G-protein coupled, leads to PKA signaling and the CREB-dependent expression of receptor activator of NF-κB ligand (RANKL) ( 252 ) and the MEF2-mediated suppression of sclerostin transcription ( 39 , 253 ); sclerostin is an inhibitor of bone formation.…”
Section: The Physiological Roles Of Salt-inducible Kinasesmentioning
confidence: 99%